The Bilateral J‐Curve in Australia: A Nonlinear Reappraisal1. (26th September 2017) - Bahmani‐Oskooee, Mohsen; Shafiullah, Muhammad; Islam, Faridul
Abstract : Since the introduction of error‐correction and cointegration techniques, the J‐curve effect implies an initial short‐run deterioration of the trade balance, followed by improvement later due to currency devaluation. In a previous study of Australia's bilateral trade, with each of her 23 partners, using the linear Autoregressive Distributed Lag (ARDL) approach we found the J‐curve effect in the model with the United Kingdom only. However, after incorporating the ARDL model that allows for nonlinear adjustment of exchange rate changes, we found the effect on four more partners – all asymmetrically. Furthermore, we document short‐run asymmetry in exchange rate changes in almost all models; short‐run adjustment asymmetry, and impact‐asymmetry in almost half of the models.